Strategi Tumbuh Dan Bersaing Di Industri Asuransi (Studi Kasus Pada BPJS Ketenagakerjaan Pekanbaru) - Nofrizal, Nofrizal (Benefit: Jurnal Manajemen dan Bisnis, 2017)
Background this research began by observing growth and rising insurance company in Pekanbaru city with many company insurance had been built in Pekanbaru city since 2014, therefore rivalry canât avoid and each company also create and arrange tactic and strategy in order to be winner from this competition.Â  BPJS Ketenagakerjaan is new entry from this insurance industry in Pekanbaru city and BJPS Ketenagakerjaan owned by government Indonesia. Aim this research to arrange and determine how BPJS Ketenagakerjaan growth and compete in insurance industry Pekanbaru city. This research use descriptive method with several step to create strategy there are Five Force Porter, IFA, EFA, Matric GE, SWOT-8K, Matric TWOS and Matric QSPM. Result this research showed the strategy Position of BPJS Ketenagakerjaan in quadrant IB (Growth) and BPJS Ketenagakerjaan can use for growth and compete using Competitive Strategy and Growth strategy